Intellectual journeys of recent, mostly "defunct" economists - Szenberg, Michael; Ramrattan, Lall, 1951- (Touro College Press (Series), 2015)
This book looks into the creative minds of some recent, mostly "defunct" economists. Many of the authors, such as Samuelson, Friedman, Galbraith, and Heilbroner, have penned popular works, while their scientific contributions were limited to the most specialized scholars. Others, such as Nobel Prize winners Modigliani, Debreu, Becker, Aumann, and Allais, delved into complex issues in human organization, economic growth and planning, socio-economic theory, and model building. Economists such as Keynes and Lowe represent world-class paragons whose influences continue to percolate in current research programs. Here we unearth their best scientific work, revealing gems that might otherwise be overlooked